Virtual brain biopsies in amyotrophic lateral sclerosis: diagnostic classification based on in vivo pathological patterns - Bede, Peter; Hardiman, Orla; Finegan, Eoin; Omer, Taha; Iyer, Parameswaran M. (My University, 2017)
Background: Diagnostic uncertainty in ALS has serious management implications and delays recruitment into clinical trials. Emerging evidence of presymptomatic disease-burden provides the rationale to develop diagnostic applications based on the evaluation of in-vivo pathological patterns early in the disease. Objectives: To outline and test a diagnostic classification approach based on an array of complementary imaging metrics in key disease-associated anatomical structures. Methods: Data from 75 ALS patients and 75 healthy controls were randomly allocated in a ‘training’ and ‘validation’ cohort. Spatial masks were created for anatomical foci which best discriminate patients from controls in the ‘training sample’. In a virtual ‘brain biopsy’, data was then retrieved from these key disease-associated brain regions. White matter diffusivity indices, grey matter T1-signal intensity values and basal ganglia volumes were evaluated as predictor variables in a canonical discriminant function. Results: Following predictor variable selection, a classification specificity of 85.5% and sensitivity of 89.1% was achieved in the training sample and 90% specificity and 90% sensitivity in the validation sample. Discussion: This study evaluates disease-associated imaging measures in a dummy diagnostic application. Although larger samples will be required for robust validation, the study confirms the potential of multimodal quantitative imaging in future clinical applications.
Keywords: Magnetic resonance imaging; Neuroimaging; Diagnosis; Neurodegeneration; Amyotrophic lateral sclerosis (ALS); Motor neuron disease; Neuroscience